Modification of the WC-Co carbide surface with high-intensity pulsed ion beam; Journal of Physics: Conference Series; Vol. 1588 : Low Temperature Plasma during the Deposition of Functional Coatings - Prima A. I. Artem Igorevich; Egorova Yu. I. Yulia Ivanovna; Pushkarev A. I. Aleksandr Ivanovich; Matrenin S. V. Sergey Veniaminovich (2020, 2020)
Title screen